Characteristics and effectiveness of group support programs for informal caregivers - a systematic review / Design und Erfolg von Gruppenschulungen für pflegende Angehörige - eine systematische Übersichtsarbeit - Fink-Heitz Margit; Behrens Johann (Sciendo, 2015)
In Germany 1,76 million people are in need of care to live at home. Most of them (1,18 mill.) receive that care from members of their own families. German informal caregiver training programs are paid for by the compulsory long term care insurance. Nevertheless there are only very few published national curricula or evaluations of training courses. Therefore we reviewed international evaluations of group support programs for informal caregivers.